2003
DOI: 10.1063/1.1589176
|View full text |Cite
|
Sign up to set email alerts
|

Occupation probability for acceptor in Al-implanted p-type 4H–SiC

Abstract: Al-implanted p-type 4H–SiC layers with different implantation and annealing temperatures are formed, and the temperature dependence of the hole concentration p(T) is obtained by Hall-effect measurements. The Al acceptor level in SiC is deep (∼180 meV), and its first excited state level calculated by the hydrogenic model is still deep (∼35 meV), which is close to the acceptor level of B in Si. Therefore, in order to determine the reliable acceptor density (NA) from p(T), the Fermi–Dirac distribution function is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Figure 2 shows the temperature dependence of the hole mobility (µ h (T )). Because at the same temperature µ h (T ) in the Mg-implanted 4H-SiC layer was only a little bit lower than the value of µ h (T ) in the Al-implanted 4H-SiC layer [3], the holes moved in the valence band, not by hopping. As a result, it is found that Mg atoms in 4H-SiC emit holes into the valence band and behave as an acceptor.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the temperature dependence of the hole mobility (µ h (T )). Because at the same temperature µ h (T ) in the Mg-implanted 4H-SiC layer was only a little bit lower than the value of µ h (T ) in the Al-implanted 4H-SiC layer [3], the holes moved in the valence band, not by hopping. As a result, it is found that Mg atoms in 4H-SiC emit holes into the valence band and behave as an acceptor.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 In order to determine a reliable value for N A using p(T) in p-type SiC, the following two attempts have been made: ͑1͒ the experimental adjustment of Hall-scattering factor for holes 12,13 and ͑2͒ the theoretical introduction of a distribution function suitable for Al acceptors. 8,9,14,15 Moreover, Al atoms with high density may disturb the valence band structure near E V , and might form an impurity band. However, the p(T) for these p-type SiC samples exhibit a typical semiconductor behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The physical properties of n-type SiC have extensively been investigated so far, [15][16][17][18][19] and those of p-type SiC have also been obtained recently. [20][21][22][23][24][25][26] In our studies, the temperature dependences of hole mobility, hole concentration, and Hall scattering factor were shown by performing Hall-effect measurement on thick p-type SiC epilayers with various doping concentrations. 24,26) Although the resistivity of p-type SiC can be estimated from these data, 24,26) it is much more useful to give an analytical expression that describes the temperature dependence of resistivity.…”
Section: © 2018 the Japan Society Of Applied Physicsmentioning
confidence: 99%